Change in Fitness and the Relation to Change in Cognition and Neuropsychiatric Symptoms After Aerobic Exercise in Patients with Mild Alzheimer’s Disease - Sobol, Nanna A. (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity has the potential to improve physical function in patients with Alzheimer’s disease (AD) and may contribute to modify disease processes and cognitive function. OBJECTIVE: The aim of this study was to investigate 1) the effect of moderate-high-intensity aerobic exercise on cardiorespiratory fitness, i.e., peak oxygen uptake (VO(2peak)) determined by direct breath-by-breath cardiopulmonary exercise test, and 2) the association between changes in VO(2peak) and changes in cognition and neuropsychiatric symptoms in patients with mild AD. METHODS: The study is based on secondary outcome analyses from the large single-blinded multi-center study ADEX (Preserving Cognition, Quality of Life, Physical Health and Functional Ability in Alzheimer’s Disease: The Effect of Physical Exercise). A preselected sub-group of 55 participants (age 52–83 years), 29 from the intervention group (IG) and 26 from the control group (CG), was included. IG performed 16 weeks of supervised moderate-to-high intensity aerobic exercise. Assessments of VO(2peak), mental speed and attention (Symbol Digit Modalities Test, SDMT), and neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI) were performed at baseline and at 16 weeks. RESULT: VO(2peak) increased 13% in the IG and a between-group difference in mean change (3.92 ml/kg/min, 95% CI 6.34–1.51, p = 0.003) was present in favor of the IG. Combined data from IG and CG showed positive associations between changes in VO(2peak) and changes in NPI (Rho = – 0.41, p = 0.042) and changes in SDMT (Rho = 0.36, p = 0.010), respectively. CONCLUSION: Aerobic exercise improves VO(2peak) in community-dwelling patients with mild AD. Furthermore, changes in VO(2peak) appear to be associated to changes in cognition and neuropsychiatric symptoms.